2016
DOI: 10.7554/elife.13410
|View full text |Cite
|
Sign up to set email alerts
|

A century of trends in adult human height

Abstract: Being taller is associated with enhanced longevity, and higher education and earnings. We reanalysed 1472 population-based studies, with measurement of height on more than 18.6 million participants to estimate mean height for people born between 1896 and 1996 in 200 countries. The largest gain in adult height over the past century has occurred in South Korean women and Iranian men, who became 20.2 cm (95% credible interval 17.5–22.7) and 16.5 cm (13.3–19.7) taller, respectively. In contrast, there was little c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
179
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(209 citation statements)
references
References 74 publications
11
179
0
6
Order By: Relevance
“…However, the secular height trend faded in many European countries [24]. We do not have current information on the secular height trend in Israel and its relation to overnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the secular height trend faded in many European countries [24]. We do not have current information on the secular height trend in Israel and its relation to overnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In some Southern European and many Latin American countries where gains are still being made in socioeconomic conditions, heights have not yet plateaued and continue to increase. Conversely, height decreases or consistent short stature persist in many LMIC between 1896 and 1996 [10]. In a detailed country analysis of India between 1975 and 2013, adult height increases are similar to those seen in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing adult height in various populations is reported extensively in the literature [10]. A recent paper of over 18.6 million participants in 1,472 population studies which analyzed measurements of height found that adult height increased substantially between 1896 and 1996, but this was unevenly distributed between men and women and amongst countries [10].…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone and insulin-like growth factor-1 (IGF-1) are regulators of childhood physical growth (Butler and Le Roith 2001) but are also implicated in brain development including brain growth and cortical maturation (D'Ercole et al 1996;Narducci et al 2018). Higher IGF-1 levels have also been reported to be associated with higher GCA (Gunnell et al 2005).…”
Section: Best-fitting Model Shown In Bold Fontmentioning
confidence: 99%